Abordagem normalizada para conversores ressonantes - Mendonça, Lucas Sangoi (2017)
Resonant converters reveal their excellence by means of the philosophy of shaping the converters waveforms in a sinusoidal fashion, allowing soft-switching, increase the operating frequency and reduce electromagnetic interference, which are important miniaturization requirements for high efficiency converters. Furthermore, applications in renewable energy sources, electric vehicles, LED, mobile devices, wireless power transfer and so on, have been recent research and make use of unique attributes of these converters. Notwithstanding, resonant converters analysis is more complex than their pwm counterparts due to multiresonant procedure in the converter, so the analytical solutions are hard to be obtained. This master’s thesis aims the development of a normalized approach for resonant converters analysis and design. The method is used to represent the system in a normalized state-space model that is independent of real circuit parameters, such as, inductances, capacitances and resistances. In addition, the normalization procedure is performed by means of an equivalence transformation, in which, a new state vector that is composed by terms as the square root of the stored energy in reactive components, is used to system modeling, making the system independently of input and operating frequency. Therefore, gain and component stress curves can be obtained for any operating point, and they can be used to converters design. Analysis and design of several converters are performed and a comparison of theoretical, simulation and experimental results is conducted. A converter selection design procedure is developed, in which, starting from specifications, it is possible to compare a number of converters and elucidate the choice of the most suitable topology. The main advantages of the methodology are: converters analysis for any operating point independently of circuit parameters; normalized design; obtaining gain and component stress curves and topologies comparison. The results can be used as theoretical basis for high efficiency systems development that operate in increased frequency, which are a trend in power electronics applications.